The development and optimisation of graphene-based biosensors devices as a commercial biosensing platform - MUHAMMAD ALI (2023)
This thesis reports the complete design, fabrication and optimisation of a graphene biosensor platform, integrating a novel Molecular Vapour Deposition (MVD) passivation process, capable for real-time electrical sensing applications. This chemical vapour deposition (CVD) graphene sensor utilises the exceptional electronic properties and remarkably high surface area-to-volume ratio of graphene. It is fabricated using microelectronic processing methods, such as photolithographic processes, physical vapour deposition (PVD) techniques and MVD deposition, and is thus scalable for manufacturing on large format wafers and multi wafer processing. These processes underwent extensive process optimisation and was characterised using microscopic and spectroscopic techniques, such as AFM and XPS, for improved device performance and homogeneity. A critical requirement of any graphene biosensor point-of-care (POC) platform is that it is able to perform in liquid environments, without degradation of the device and associated signal changes in the device related to this liquid-induced device degradation. MVD deposition and etch process was developed to protect the metal interconnect tracks of the device chip from harsh chemicals and short circuiting, and making it suitable for liquid-based sensing. This passivation technique also greatly improves graphene device homogeneity, reducing the organic contaminants from the graphene surface by approximately 50%. This makes them highly applicable for use in POC diagnostics, and the latter part of this thesis details the development of functionalised sensors and their application in chemical sensing. A handheld connector platform was designed and fabricated for the graphene-based sensor chip, allowing for different applications, such as graphene functionalisation and electrical analysis, across one sensing platform. Modular adapters were created for the connector, allowing for selective address of individual graphene channels on the same chip, allowing alternative functionalisation of each channel and hence the capacity for multiplexed sensing. For more in depth characterisation of the electrical properties of graphene devices, a graphene Hall bar device was fabricated, and electrical measurements performed to extract the mobilities and carrier densities from the devices. In order to turn the graphene device into a biosensor, several different functionalisation methods were applied to the graphene device, with an investigation of how each functionalisation process affects the electrical performance of the graphene performed. Characterisation of non-covalent and covalent attachment of amino functional layers, showed that non-covalent functionalisation of amino functional layers resulted in a ~75% increase in graphene resistivity, from 30×10-6 Ω.cm to 53×10-6 Ω.cm, whilst covalent functionalisation produced a ~600% resistance increase, from 36×10-6 Ω.cm to 256×10-6 Ω.cm. Functionalisation processes have been developed for the sensing of Li+ ions, an active chemical found in the treatment for bipolar disorder and mania. The sensor was able to detect changes in Li+ ion concentration from 0.1 – 2.0 mM. Previously developed amino functional layer processes have been characterised and implemented into graphene devices, showing real-time functionalisation capabilities and understanding the bonding mechanics between the functional layers and the graphene.